Kekerabatan Bentuk Kosakata Perabot Dapur dalam Bahasa Arab Sudan dan Suriah - Darsita Suparno; Ali Qosebaty (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
The study is aimed at investigating differences of Amiyah Sudanese and Syrian Arabic lexical forms and meanings in the field of kitchen appliances. It is a study of comparative historical linguistics that uses corpuses of both languages obtained from four Sudanese and Syrian native speaker students who utilize these tools in their everyday modern live. The authors collect the data by themselves applying their own compiled vocabulary list and Swadesh vocabulary list. The findings show that “kitchen appliances@ vocabularies in the Sudanese and Syrian are related to each other. This is evidenced by the the word pairs which (a) are identical or cooccurrence; (b) have a phonemic correspondence or recurrence; and (c) have phonetical similarity with one phoneme difference. In addition, the kitchen appliances usage changes too along with the need in identifying the new words or terms for the new kitchen appliances. It is concluded that the lexical form of Sudanese and Syrian Arabic is systematically compatible, in terms of sound aspects; however sounds of the Sudanese language change in the Syrian vocabulary. Studi ini bertujuan menyelidiki perbedaan bentuk dan makna dari kosakata bahasa Amiyah Sudan dan bahasa Arab Suriah dalam kosakata dapur dan apa saja bentuk dan makna kata-kata majemuk dalam peralatan dapur ini. Penelitian ini merupakan kajian Linguistik Historis Komparatif dengan menggunakan data dari kedua bahasa tersebut yang diperoleh dari empat mahasiswa penutur jati Sudan dan Suriah yang menggunakan alat masak tersebut setiap hari di era modern. Data dikumpulkan dengan mengacu pada daftar kosakata bahasa Swadesh dan daftar kosakata lainnya. Penelitian ini memperlihatkan bahwa kosakata